Students’ Perception Towards Drama Technique to Reduce Speaking Anxiety of Seventh Semester Students of English Department at UNISMA. - Maslindatun Ni'mah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: This study aimed to describe students' perceptions toward drama techniques to reduce speaking anxiety in speaking English. Students' anxiety is a problem that is often found in learning English, especially in speaking. Speaking anxiety has an impact on the students' speaking skills. This study was conducted with 20 seventh semester students of the English Department at University of Islam Malang who had taken drama courses. This research was descriptive qualitative. The researcher collected the data by giving questionnaire. The questionnaire consisted of 20 items related to drama and speaking anxiety. Those questionnaire consisted of 2 parts. For questions number 1-10 it is students response toward drama activity in their English lessons, and questions number 11-20 it is students’ perception toward the impacts of using drama presentations. The researcher found that 80% students agree that they are now more confident when speaking English in public. Keywords: Students’ Perception, Drama Technique, Speaking Anxiety.